2022
DOI: 10.1063/5.0076993
|View full text |Cite
|
Sign up to set email alerts
|

Ambient pressure x-ray photoelectron spectroscopy setup for synchrotron-based in situ and operando atomic layer deposition research

Abstract: A setup for studies of photoelectron circular dichroism from chiral molecules in aqueous solution Review of Scientific Instruments 93, 015101 (2022);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The gas inlet system is done via a so-called double-cone system, where the inner cone has an aperture through which electrons enter the analyser and an outer, larger-diameter cone directs gas towards the sample surface from the same direction as the analyser (Kokkonen et al, 2021). Recently, the dedicated ALD cell at SPECIES was designed and built to achieve gas flow that mimics the flow in real ALD reactors (Kokkonen et al, 2022). APXPS has proven to be a very powerful tool for studying in situ and operando studies of ALD cycles and for revealing reaction steps otherwise unobservable with traditional methods (D'Acunto et al, 2022;Temperton et al, 2019;Timm et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The gas inlet system is done via a so-called double-cone system, where the inner cone has an aperture through which electrons enter the analyser and an outer, larger-diameter cone directs gas towards the sample surface from the same direction as the analyser (Kokkonen et al, 2021). Recently, the dedicated ALD cell at SPECIES was designed and built to achieve gas flow that mimics the flow in real ALD reactors (Kokkonen et al, 2022). APXPS has proven to be a very powerful tool for studying in situ and operando studies of ALD cycles and for revealing reaction steps otherwise unobservable with traditional methods (D'Acunto et al, 2022;Temperton et al, 2019;Timm et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In core level X-ray Photoelectron Spectroscopy (XPS), this dependence can be exploited to identify the chemical environments that are present in the sample. XPS is particularly well suited for the analysis of complex surfaces, and it plays an important role in the study of heterogeneous catalysis, corrosion, environmental degradation, or the manufacture of surface coatings. However, the interpretation of XPS spectra is challenging, which has motivated the development of computational techniques for calculating core electron binding energies from first principles. …”
Section: Introductionmentioning
confidence: 99%
“…XPS is particularly well suited for the analysis of complex surfaces, and it plays an important role in the study of heterogeneous catalysis, 1-4 corrosion, [5][6][7] environmental degradation, [8][9][10] or the manufacture of surface coatings. [11][12][13][14] However, the interpretation of XPS spectra is challenging, which has motivated the development of computational techniques for calculating core electron binding energies from first principles. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] For the prediction of absolute core electron binding energies in periodic solids, two kinds of methods have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Although the relatively high pressures present in the ALD process (10 −4 to 10 mbar), the comparably high amount of impurities, and the typical lack of a high crystalline order have prevented a classic surface science approach like that applied to deposits grown using physical vapor deposition techniques (e.g., molecular beam epitaxy), an increasing number of operando and in situ (also referred as in vacuo) studies, have been reported in the last years. For instance, operando studies have been recently performed using flow-type reaction cells in differentially pumped X-ray photoelectron spectroscopy (NAP-XPS) devices [33][34][35]. Due to the characteristic high pressures of ALD processes, especially when a carrier gas is used, these operando and time-resolved XPS experiments are typically limited to synchrotron facilities, although some experiments have been carried out at standard NAP-XPS setups [36,37].…”
Section: Introductionmentioning
confidence: 99%